THE LABYRINTH OF GENDER TRAJECTORY TO SELF-ACTUALISATION: A STUDY ON THE PSYCHOLOGICAL TRAUMA OF TRANS WOMEN IN SELECT INDIAN MEMOIRS - A DEVELOPMENTAL APPROACH - Joy Hepzibah C; Dr. Arul J (The Bioscan, 2024)
“We are all assigned a gender at birth. Sometimes that assignment doesn’t match our inner truth, and there needs to be a new place–a place for self-identification.” (Geena Rocero). Despite the growing exposure to intellectual advancements, society is hierarchically constructed based on caste, creed, religion gender and class. Amidst all, gender issues have remained unresolved for many years in the heteronormative set-up. And the sexual minorities in India exceed the established gender frameworks of the society. Being socially and spatially marginalized, the predicament of gender non-binarism is still a problematic issue and the concept of gender binomial prevails in mainstream society which leads the TGNC (Transgender and Gender Non-conforming People) into stigmatization, the act of trans-bashing. Since the morbidity is high in MF (Male to Female) trans individuals, transwomen have been chosen for the study who possess the male anatomy and female behavioural traits and feminine sense of identity. This makes society tag them as social deviants or as abhorrent people. The consecutive events of stigma encountered by the transwoman reciprocate the psychological trauma in every stage of their life. The coming out of the transgender can be compared to a moth which struggles to pop out of its cocoon. The labyrinth of the trajectory of transwomen from the state of self-discovery to self-identification is crucial and can be formatively categorized into different stages as self-discovery, disclosure, socialization, self-identification and Self-acceptance. With all these stages, they go through different psychological trauma like gender dysphoria or incongruence, internalized transphobia and suppression of identity till the coming out. This study critically investigates the stages of coming out of trans women and the psychological trauma they face in different stages of their life and has been reflected through trauma narrative in the select narratives of transgender writers like A. Revathi, Living Smile Vidya and Kalki Subramaniam and also reiterates the fact that trauma narrative can be an avenue to attain self-actualization.